The class III peroxidase gene family is involved in ascorbic acid induced delay of internal browning in pineapple - Hou, Xiaowan; Lu, Zhiwei; Hong, Keqian; Song, Kanghua; Gu, Hui; Hu, Wei; Yao, Quansheng (Frontiers in Plant Science, 2022)
Excessive production of reactive oxygen species (ROS) leads to potential toxicity in an organism. Class III peroxidases (PRXs) play an important role in maintaining ROS homeostasis in plants. Internal browning (IB) limits industrial development of pineapple, which is the third most important fruit trade in the world. IB is mainly caused by ROS, and the mechanism underlying IB is still unknown from the perspective of ROS. Here, we soaked pineapples in ascorbic acid after harvest and before storage to decrease excessive ROS and polyphenol oxidase (PPO) activity, ultimately restraining the spread and deterioration of IB. Using phylogenetic analysis; we identified 78 pineapple PRX genes (AcPRXs) and divided them into five subgroups. Gene structure analysis indicated that the exon numbers ranged from 2 to 14, and conserved motif analysis verified that all of the AcPRXs identified here have standard peroxidase domains. Analysis of duplication events suggested that tandem and segmental duplication events may have played equal and important roles in expanding the AcPRX family. Comprehensive transcriptomic analysis uncovered that AcPRXs may play an important role in negatively regulating the occurrence of IB. In summary, we found that ROS scavenging delayed IB occurrence. The results of characterized AcPRX family revealed that AcPRXs family responded to growth and development, and negatively regulated to IB occurrence in storage stage. This research provides potential target genes for future in-depth analysis of the molecular mechanisms underlying IB and contributes to develop IB-resistant pineapple varieties.